Cross-Correlation Video Recording of Gas-Vapor-Droplet Two-Phase Flows; The 9th International Forum on Strategic Techology (IFOST-2014), September 21-23, 2014, Cox's Bazar, Bangladesh - Volkov R. S. Roman Sergeevich; Vysokomornaya O. V. Olga Valeryevna; Zhdanova A. O. Alena Olegovna; Strizhak P. A. Pavel Alexandrovich (Publication Only Papers, 2014)
Title screen